Stress and coping strategies among NHS executives in sustainability and transformation partnerships. Issue 1 (2nd January 2020) - Brown, Craig; Hendy, Jane; Wang, Catherine L
Abstract : This study investigated stress experienced by NHS executives and their coping strategies following the development of sustainability and transformation partnerships (STPs). Lazarus and Folkman's (1984) transactional model of stress and coping was used to identify a range of stressors and coping strategies deployed by NHS executives to mitigate stress. An inductive qualitative approach was adopted using interview data, aiming to distinguish potentially harmful stressors from benign stressors and to discuss emotion-based and problem-based coping strategies. Finally, the authors strived to make clear recommendations for NHS England to develop leadership capability regarding inter-role conflict and the development of a regional culture of resilience among system-level executives.